(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes, from both scientific and practical perspectives, the artistic and technical possibilities of watercolor technology in the process of creating still life compositions, as well as the main methods of ensuring compositional integrity. The study examines in depth the unique transparency of watercolor paints, optical effects formed through layered color application, relationships between light and shadow, and their influence on compositional structure. The article also reveals the scientific foundations of defining a compositional center, maintaining rhythm and balance, creating color harmony, and forming spatial solutions in still life work.